Porosity and Permeability Modification by Diagenetic Processes in Fossiliferous Sandstones of the Baram Delta, Sarawak Basin, Malaysia - Ben-Awuah, Joel; Padmanabhan, E. (Springer, 2015)
The main productive units in the Baram Delta are cycles V and VI Upper to Middle Miocene sandstones. Significant fossiliferous intervals have been identified within these units. The objective of this paper was to investigate the impact of diagenetic processes on fossiliferous sandstones and how such modifications to the fossils influence porosity and permeability. Two wells from two fields in the Baram Delta were evaluated using thin sections, CT scan imaging, SEM, EDX, spot permeability, and poro-perm. Intragranular pores have been formed within the fossils by diagenetic processes. The uplift of the Rajang Group accretionary prism to form the Rajang Fold-Thrust Belt facilitated the creation of these pores by bringing the reservoir sandstones into the telogenetic regime where dissolution by meteoric water is the major porosity-forming process. Spot permeability in the fossiliferous part of the sandstone ranges between 606 and 879 mD, whereas the relatively non-fossiliferous part has spot permeability values ranging between 305 and 521 mD. This represents a porosity and permeability enhancement of 50–60 % in the fossiliferous part. This enhancement is attributed to the intragranular porosity formed within the fossils by diagenetic processes. Porosity and permeability range between 18 and 30 % and 662 and 683 mD in fossiliferous horizons (FH) and 13 and 27 % and 10 and 529 mD in non-fossiliferous horizons, respectively.